CORPORATE STRATEGIES AND GREEN FINANCE MARKETING IN UZBEKISTAN (Журнал «Маркетинг», 2025)
This thesis argues that building a green economy in Uzbekistan requires more than technology and green finance to attract foreign investment. Green marketing is essential to accelerate sustainable practices by businesses and society.